Order for payment procedure: What to do when the defendant cannot be personally served? - Rincón Almeyda, Ariel (DIXI, 2017)
Theme and scope: the order for payment procedure has been one of the legal institutions that has generated the most comments and raised concerns in the Colombian legal community since it was proposed as an institution to be incorporated into the General Code of Procedure. This procedural institution dates back to the Middle Ages and has been historically introduced in different procedural systems. Characteristics: some of the characteristics identified are speed, the possibility of a final judgment, and its strictly pecuniary nature. Findings: however, the incorporation of this legal institution entails the problem of its disuse, because, when the defendant cannot be served, the legal option that the plaintiff has is to withdraw the claim and initiate another type of legal action. Conclusions: the purpose of this article is to prove that the limitations imposed on the form of summons in the order for payment procedure lead to the denial of justice while the citizen ends up not using the order for payment procedure, but traditional methods in order to obtain a writ of execution.